The Association Between the Family’s Income, number of family, and Knowledge with Stunting - Carvalho, Marcos; Anatolia Soares Maia Exposto, Levi; Jorge Pereira, Santiago; Elvis Fátima, Tomas; Conceição Pacheco, Aniceto da (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Timor-Leste has the highest prevalence of stunting compared to countries in the Asia Region and the sixth highest rate globally. RAEOA is the highest stunting number three in Timor-Leste. Objective: The objective is to find out the Association between the mothers' Education level, Occupation, family income, Total number of families, and mothers' knowledge of stunting. Method: The research design used quantitative research with a survey design using a selective cross-sectional approach. The sample is mothers who have children under five years. Data were analyzed using SPSS. Chi-square test for the single association and linear regression for multivariate association. Result and Discussion: The results found that the Association between the mother’s education and occupation is not significant with stunting. The Association between Family Income, the Number of Families, and Mother’s Knowledge is significant with stunting. A strong association between the Mother's Education, Occupation, Family Income, number of Families, and Mother's Knowledge with stunting. Conclusion: Concluded that the role of mothers in the golden phase is very important to prevent stunting in children. It is recommended that the Health Center and District Health Service intervene with health promotion programs to increase knowledge, prepare healthy food practices, and work with related institutions to solve the problem of stunting in Timor-Leste